2020
DOI: 10.3390/ijerph17186811
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Phthalates’ Action on Reproductive Processes and Reproductive Health: A Literature Review

Abstract: The production of plastic products, which requires phthalate plasticizers, has resulted in the problems for human health, especially that of reproductive health. Phthalate exposure can induce reproductive disorders at various regulatory levels. The aim of this review was to compile the evidence concerning the association between phthalates and reproductive diseases, phthalates-induced reproductive disorders, and their possible endocrine and intracellular mechanisms. Phthalates may induce alterations in puberty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(93 citation statements)
references
References 247 publications
(326 reference statements)
1
91
0
1
Order By: Relevance
“…Altogether, these observations suggest that the effects induced in mice by adult exposure to low doses of phthalates on cyclicity and behavior might be relevant for human reproduction. It is interesting to note that epidemiological studies reported associations between exposure to phthalates and reproductive issues, including premature ovarian failure ( Hlisníková et al. 2020 ) and low interest in sexual activity ( Barrett et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these observations suggest that the effects induced in mice by adult exposure to low doses of phthalates on cyclicity and behavior might be relevant for human reproduction. It is interesting to note that epidemiological studies reported associations between exposure to phthalates and reproductive issues, including premature ovarian failure ( Hlisníková et al. 2020 ) and low interest in sexual activity ( Barrett et al.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these observations suggest that the effects induced in mice by adult exposure to low doses of phthalates on cyclicity and behavior might be relevant for human reproduction. It is interesting to note that epidemiological studies reported associations between exposure to phthalates and reproductive issues, including premature ovarian failure (Hlisníková et al 2020) and low interest in sexual activity (Barrett et al 2014). In this context, it is important to indicate that since 1975 sexual health has been included by the World Health Organization (WHO) as part of reproductive health, and it is recognized that sexual dysfunction may affect not only reproduction but also mental and general health, well-being, and maturation (WHO 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary DEHP level was positively associated with blood pressure in childhood, and the level of DEHP was associated with diabetes and serum insulin levels [ 11 ]. In additional to animal experiments, systemic review of both epidemiological and animal toxicity studies concluded that DEHP and DBP exposure may lead to adverse reproductive health outcomes in both males and females [ 6 , 10 , 12 ]. DEHP and DnBP had anti-androgenic effects in males [ 10 , 12 ], which could affect testicle function, and it may lead to male fertility disorders and testicular dysgenesis syndrome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In additional to animal experiments, systemic review of both epidemiological and animal toxicity studies concluded that DEHP and DBP exposure may lead to adverse reproductive health outcomes in both males and females [ 6 , 10 , 12 ]. DEHP and DnBP had anti-androgenic effects in males [ 10 , 12 ], which could affect testicle function, and it may lead to male fertility disorders and testicular dysgenesis syndrome [ 12 ]. Additionally, the biochemical mechanism through which cardiotoxicity occurs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalates are also known as a class of EDCs with estrogenic and antiandrogenic effects [16]. Phthalates or their metabolites mainly affect the human endocrine and reproductive system, leading to developmental and reproductive impairment [17], growth retardation [18,19], neurodevelopmental problems [20], allergies and asthma [21].…”
Section: Introductionmentioning
confidence: 99%